Formation of water-in-diesel oil nano-emulsions using high energy method and studying some of their surface active properties - A.M. Al-Sabagh; Mostafa M. Emara; M.R. Noor El-Din; W.R. Aly (Egyptian Journal of Petroleum)
In this work, formations of water-in-diesel oil nano-emulsions using water/mixed nonionic surfactant/diesel oil system have been studied. The high energy emulsification method was used to form three emulsions using different water contents: 5%, 10% and 14% (v/v) namely; E1, E2 and E3, respectively. These nano-emulsions were stabilized with emulsifiers having different Hydrophilic–Lipophilic Balance (HLB) namely; span 80 (HLB = 4.3), emarol 85 (HLB = 11) and their mixture (SE) with HLB = 10. The effect of water on the droplet size formation has been investigated. The interfacial tension and thermodynamic properties of the individual and emulsifiers blends have been studied. The interfacial tension (γ) measurements at 30 °C were used to determine the critical micelle concentration (CMC) and surface active properties of these emulsifiers. The water droplet sizes were measured by dynamic light scattering (DLS). From the obtained data, it was found that, mean sizes between 19.3 and 39 nm were obtained depending on the water content and concentration of blend emulsifiers (SE). Also, the results show that, the interfacial tension (γ) gives minimum value (10.85 mN/m) for SE comparing with individual emulsifier (17.13 and 12.77 mN/m) for span 80 and emarol 85, respectively. The visual inspection by TEM showed that the obtained results support the data obtained by dynamic light scattering.